A multicenter, open‐label, single‐arm study of anamorelin (ONO‐7643) in advanced gastrointestinal cancer patients with cancer cachexia. Issue 23 (15th August 2019) - Hamauchi, Satoshi; Furuse, Junji; Takano, Toshimi; Munemoto, Yoshinori; Furuya, Ken; Baba, Hideo; Takeuchi, Manabu; Choda, Yasuhiro; Higashiguchi, Takashi; Naito, Tateaki; Muro, Kei; Takayama, Koichi; et al.
Abstract : Background: Cancer cachexia is characterized by weight loss and is associated with increased morbidity and mortality in patients with cancer. Anamorelin (ONO‐7643; ANAM) is a novel and selective ghrelin receptor agonist that improves appetite, lean body mass (LBM), body weight, and anorexia. Methods: This multicenter, open‐label, single‐arm study investigated the efficacy and safety of 100 mg anamorelin in 50 Japanese patients with advanced and unresectable gastrointestinal (colorectal, gastric, or pancreatic) cancer. ANAM was administered once daily over 12 weeks. The primary endpoint was the proportion of patients that maintained or gained LBM over the course of the study. Secondary endpoints included changes in LBM, body weight, quality of life (QoL), and nutritional status biomarkers. Results: The proportion of patients who responded to treatment was 63.3% (95% CI, 48.3%‐76.6%), with a least square mean ± SE change in LBM and body weight from baseline of 1.89 ± 0.36 kg and 1.41 ± 0.61 kg, respectively. Appetite‐related questions on the QoL questionnaire showed that ANAM improved appetite. Adverse events occurred in 79.6% of patients, and the most common treatment‐related adverse events were increased γ‐glutamyl transpeptidase (8.2%), diabetes mellitus (6.1%), hyperglycemia (6.1%), and prolonged QRS complex (6.1%). Conclusions: ANAM improved anorexia and patients' nutritional status, resulting in rapid increases in LBM and body weight in patients with advanced gastrointestinal cancer who had cancer cachexia. ANAM treatment was well tolerated over 12 weeks. ANAM is a potential clinically beneficial pharmacotherapeutic option for patients with advanced gastrointestinal cancer who have cancer cachexia. Abstract : The receipt of 100 mg anamorelin increases lean body mass and improves symptoms of anorexia and nutritional status in patients with advanced gastrointestinal cancer who have cancer cachexia. Anamorelin is well tolerated in these patients.